Detection of monoamine oxidase B using dark-field light scattering imaging and colorimetry. Issue 88 (19th October 2022) - Zhang, Duoduo; Jiang, Nan; Li, Peng; Zhang, Yusheng; Sun, Shihao; Mao, Jian; Liu, Songqin; Wei, Wei
Abstract : Detection of MAO-B using dark-field light scattering imaging and colorimetry based on localized surface plasmon resonance induced by silver deposited gold nanostars. Abstract : Sensitive detection of monoamine oxidase B (MAO-B) is crucial to the clinical diagnosis of neurodegenerative diseases. Here, a dual-mode strategy for detection of MAO-B with dark-field light scattering imaging and colorimetry was designed based on localized surface plasmon resonance induced by silver deposited gold nanostars.